Laparoscopic myomectomy – The importance of surgical techniques - Dumitrașcu, Mihai Cristian; Nenciu, Cătălin-George; Nenciu, Adina-Elena; Călinoiu, Amalia; Neacșu, Adrian; Cîrstoiu, Monica; Șandru, Florica (Frontiers in Medicine, 2023)
Laparoscopy is a routine procedure for benign gynecological tumors. Although the laparoscopic approach for myomas is a common procedure, it can be challenging. To improve outcomes, research regarding port access, suture type, morcellation, and complication management remains ongoing. Myomectomy is the main surgical option for patients seeking uterus-sparing procedures to maintain future fertility. The laparoscopic technique is the most important in these cases, given that possible complications can impact fertility and pregnancy outcomes. Herein, we reviewed and collated the available data regarding different suture techniques, including advantages, difficulties, and possible long-term impacts.